Investigation of structural and multiferroic properties of three phases of BiFeO3 using modified Becke Johnson potential technique. (November 2017) - Sagar, Elle; Mahesh, R.; Pavan Kumar, N.; Venugopal Reddy, P.
Abstract: Electronic band structure, ferroelectric and ferromagnetic properties of Cubic, Tetragonal and Rhombohedral (hexagonal axis) phases of multiferroic BiFeO3 compound has been investigated using first-principles calculations under the generalized gradient (GGA) and TB-mBJ semi local (Tran-Blaha modified Becke-Johnson) potential approximations using WIEN2k code. For this purpose, the total energies were calculated as a function of reduced volumes and the data were fitted to Brich Murnaghan equation. The estimated ground state parameters are found to be comparable with those of experimental ones. The semiconducting behavior of the material was obtained using TB-mBJ method in the spin polarized mode. Analysis of the density of states indicates that the valence band consists of Fe-d and O-p states, while the conduction band is composed of Fe-d and Bi-p states. The analysis of electron localization function shows that stereochemically active lone-pair electrons are present at Bi sites of Rhombohedral and Tetragonal phases and are responsible for the displacements of Bi atoms from the centro-symmetric to the non-centrosymmetric structure leading to the exhibition of ferroelectricity. Further, it has been concluded that the "lone pair" may have been formed due to the hybridization of 6s and 6p atomic orbitals with 6s 2 electrons filling one of the resulting orbitals in Bi. The Polarization and the magnetic properties including susceptibility were obtained. The calculated magnetic moments at the iron sites are not integer values, since Fe electrons have a hybridization interaction with the neighboring O ions. Highlights: Structural, electronic and multiferroic properties of three phases of BiFeO3 are investigated. Three types of methods like GGA, TB-mBJ and TB-mbj + SOC are used to do the calculations. Magnetic susceptibility Vs Temperature measurements are done using Boltztrap Code.